Housing Society Management, Authentication and Security App (International Journal of Engineering and Computer Science, 2017)
The standard of living in urban areas such as towns and cities has increased so much that most of the people are living in a housing society. When a person moves into a new housing society he is unaware of the various facilities provided by the society and his surroundings .Also a person who is already a resident of the society may have issues concerning whom to contact for various repair works, report his grievances, security issues etc. There is no proper platform for the resident to communicate with the admin. Housing Society Management, Security and Authentication app provides the solution by offering a platform to share issues between residents and the society managers which leads to rapid issue resolution and fewer misunderstandings. In the current scenario there is no proper alert mechanism to inform residents in case of emergencies such as gas leakage. Keeping track of people visiting the housing society is also a herculean task. Our project resolves these issues by making use of gas sensors and RFID technology